Fluctuations of MS births and UV‐light exposure. (12th September 2012) - Verheul, F.; Smolders, J.; Trojano, M.; Lepore, V.; Zwanikken, C.; Amato, M. P.; Grand'Maison, F.; Butzkueven, H.; Marrosu, M.; Duquette, P.; Comi, G.; Izquierdo, G.; et al.
<x xml:space="preserve">Abstract</x> Background Patients with multiple sclerosis (MS) are more frequently born in spring when compared to autumn. Fluctuation of UV‐light has been hypothesized to drive this phenomenon. Aim To assess the correlation between fluctuation of sunlight and birth season in persons with MS. Methods For this record‐linkage study, we collected from the international MSBase and the Italian MS iMed‐web databases the dates of birth of 11, 415 patients with MS from 36 centres from 15 countries worldwide and compared these to dates of live‐births from national registries. From all participating sites, we collected data on UV‐light fluctuation and assessed its correlation with seasonal fluctuation in MS births. Results Compared with the reference cohort, an increased proportion of persons with MS were born in spring and a decreased proportion in autumn (odds ratio (OR) to be born in spring versus autumn = 1.158, χ2 = 36.347, P < 0.001). There was no significantly increased fluctuation of MS births with increased quartile of ambient UV‐light fluctuation (Ptrend = 0.086). Conclusion Seasonal fluctuation of MS births as found in this worldwide cohort of patients with MS did not correlate with variation in seasonal fluctuation of UV‐light. Most likely, it results from a complex interplay between fluctuation of sunlight, behavioural factors, other environmental factors and (epi)genetic factors.